Decreasing emission factor of pollutants in an oil refinery by renovating the furnace design - A. Zabihi; M.R. Raazaitabari (Global Journal of Environmental Science and Management)
The significant consumption of gas in the World results in the emission of greenhouse gases into atmosphere. Abadan refinery has always been the biggest and oldest oil refinery in the Middle East and has a variety of refined products. After six months of collecting data about pollutant concentration emitted from a stack of old furnaces of units 75 and new unit 200, the emission factor of the pollutant was calculated. The result showed that the emission factor of some hazardous pollutants emitted from old unit 75 was tremendously higher than that of unit 200. This study suggests the installation of a forced fan to provide the excess air and a feed temperature controlling system to control fuel gas consumption. These would make the fuel combustion complete and decrease its consumption. Meanwhile, further results showed that the renovation of unit 75 could lead to a significant annual reduction of some pollutants such as CO, H2S, and CxHx to 66 ton, 3 ton, and 800 kg, respectively; this would increase the emission rate of pollutant SO2 up to 150 ton annually. Finally, the new data of pollution coming from unit 75 were compared to pollution standard at American refineries. Results showed that the emission factor of most pollutants were below the American standard limits. However, the emission factor of sulfur dioxide emitted from upgraded furnace of unit 75 surpassed the American standard values. Fuel gas needs to be free of hydrogen sulfide in order to decrease SO2 emission in unit 75. It is predicted that the renovation of other 11 old furnaces belonging to Abadan refinery will result in significant decrease of pollutants CO, CxHx and H2S up to 320, 94 and 76 ton annually.